Canva Learning Media Development Workshop for Teachers of SMPK Adisucipto Penfui Kupang: Workshop Pengembangan Media Pembelajaran Canva bagi Guru-guru SMPK Adisucipto Penfui Kupang - Ch. Krisnandari Ekowati; Siprianus Suban Garak; Aleksius Madu; Imelda Hendriani Eku Rimo; Fransiska Atrik Halim (Universitas Lancang Kuning, 2024)
The problems found were (1) there are still teachers who have not been able to develop technology-based learning media; (2) most teachers have never had the opportunity to take part in a technology-based learning media development workshop; (3) The school's desire to improve teacher quality is very high, but is constrained by funding. So the solution provided by the PKM team was to carry out a Canva-based learning media development workshop. The methods used in this activity are lecture, discussion, question and answer, and practice. The material provided is getting to know the Canva platform, getting to know the applications that are integrated with Canva, and how to develop interesting Canva learning media. The evaluation results obtained were 58.33% of participants felt very satisfied, 41.67% of participants felt satisfied and no participants felt less satisfied or dissatisfied. These results show that PKM activities are running well.